Vade-mecum van den socialistischen propagandist. Wetgevende verkiezingen van 1925. [met voorw. van J. van Roosbroeck. Bijdrn van F. Dardenne, P.H. Spaak, M. Somerhausen e.a.] (Volksdrukkerij, 1924)
Algemeene raad van de B.W.P.